Individual preparedness for natural disasters: a cross-sectional study from Portugal. (30th September 2020) - Ferreira, R; Rodrigues, C; Correia-Santos, P; Moreira, M; Silva, S
Abstract: Background: Individual preparedness is critical in mitigating the adverse effect of natural disasters (ND). Factors influencing preparedness are complex and multifaceted, with certain groups having different needs and vulnerabilities. We aimed to explore the factors associated with individual ND preparedness in residents from Vila Nova Gaia (VNG), Portugal. Methods: A cross-sectional study was conducted in VNG, Portugal, in January 2020 (N = 192; ≥18 years). Data on sociodemographic characteristics, risk perception, and preparedness were collected using a structured questionnaire, in parishes randomly selected. Crude and adjusted odds ratio (OR) and respective 95% confidence intervals (CI) were estimated using logistic regression models. Results: About 33% of participants aged ≥65 years and 66% had low education. Results show that 20% had a survival kit. In univariate comparisons, older (11% vs. 24%, p=.029) and lower educated participants (≤12th grade: 13% vs. >12th grade: 32%, p=.002) were less likely to have a survival kit; only education remained associated after adjustment for age (OR = 2.61, 95%CI:1.22-5.58). About 21% had a family plan for disaster and only education level is associated (≤12th grade: 17% vs. >12th grade: 29%, p=.040). Almost 35% had a family member with basic life support training; older age, lower education and higher risk perception were negatively associated and these remained after adjustment (≥65 vs. <65 years OR = 0.36, 95%CI:0.16-0.77; ≤12th vs. >12th grade OR = 0.40, 95%CI:0.21-0.78; risk perception OR = 0.66, 95%CI:0.45-0.95). Only 22% participated in community drills; older people (6% vs. 31%, p<.001) and less educated (14% vs. 39%, p<.001) were less likely to have ever participated, which persisted in multivariate model. Conclusions: Our findings revealed a low-level of ND preparedness, and older and less educated people seem to present worse preparedness. This highlights the need to design specific public health interventions among these groups. Key messages: We found a low-level of individual preparedness for natural disasters in VNG, Portugal. Community-based public health interventions are needed to improve individual preparedness for natural disasters. Specific interventions targeting older and less educated people should be designed to decrease their vulnerability facing a natural disaster.